2013
DOI: 10.3382/ps.2013-03072
|View full text |Cite
|
Sign up to set email alerts
|

Screening of quinolone antibiotic residues in chicken meat and beef sold in the markets of Ankara, Turkey

Abstract: This study aimed to find the effects of quinolone antibiotics in chicken and beef used in Ankara, Turkey. Total number of 127 chicken and 104 beef meat samples were collected randomly from local markets for analysis. Extraction and determination of quinolones were made by ELISA procedure. One hundred eighteen of 231 (51.1%) examined chicken meat and beef samples were found to contain quinolone antibiotic residue. Among the chicken meat and beef samples, 58 (45.7%) of chicken meat samples and 60 (57.7%) of beef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 27 publications
2
34
4
3
Order By: Relevance
“…In fact, the majority of medicines sold in Nigeria are of poor quality and the fact that Cameroon is one of the countries where these products are sold, could explain these results (Messomo 2006;Tomdieu, 2013). Percentages of the contamination higher than those recorded in this study were also noted by Ibrahim et al (2009), Er et al (2013) and Abdul Samad et al (2014) in Nigeria Dipeolu and Alonge (2002) and Morshdy et al (2013) in the Dakahlia Province in Egypt (2%) and Nigeria (16.11%) respectively. The proportion of cattle carcasses contaminated with penicillin residues (18.81%) is significantly higher than those contaminated with oxytetracycline residues (1.49%).…”
Section: Discussioncontrasting
confidence: 37%
“…In fact, the majority of medicines sold in Nigeria are of poor quality and the fact that Cameroon is one of the countries where these products are sold, could explain these results (Messomo 2006;Tomdieu, 2013). Percentages of the contamination higher than those recorded in this study were also noted by Ibrahim et al (2009), Er et al (2013) and Abdul Samad et al (2014) in Nigeria Dipeolu and Alonge (2002) and Morshdy et al (2013) in the Dakahlia Province in Egypt (2%) and Nigeria (16.11%) respectively. The proportion of cattle carcasses contaminated with penicillin residues (18.81%) is significantly higher than those contaminated with oxytetracycline residues (1.49%).…”
Section: Discussioncontrasting
confidence: 37%
“…In Iran, using HPLC, Salehzadeh et al (2007) investigated 270 chicken tissues samples from 90 broiler farms and found enrofloxacin mean concentrations of 18.32 ± 32.29, 18.34 ± 12.36 and 26.06 ± 19.52 μg kg −1 in muscle, liver and kidney samples respectively. In Turkey, Er et al (2013) found 45.7% of the chicken breast samples positive for quinolones by ELISA. In Saudi Arabia, using HPLC, Al-Mustafa and Al-Ghamdi (2000) detected 35.0% and 56.7% of quinolone residues in muscles and livers respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Non-observance of withdrawal period has however, been linked to detection of unacceptably high levels of aminoglycosides, betalactams, chloramphenicol, macrolides, sulphonamides, tetracyclines and fluoroquinolone, residues in poultry eggs, milk and meat products both in Ghana [27] and other parts of the world [51][52][53]. The refusal of farmers to follow recommended withdrawal period, would not only lead to the continual detection of these residues in poultry products, but also contribute to the increasing resistant strains of pathogenic bacterial agents aside causing irritation and hypersensitivity reactions in humans [7,40,54].…”
Section: Discussionmentioning
confidence: 99%